Some Evidenceon Exchange Rate Determination in Major Industrial Countries - Sun, Yan (IMF Working Papers; Working Paper ;, 1997)
This paper examines the role of long-run monetary and cyclical factors in determining exchange rate movements. Results of empirical study using a data set that includes Canada, Germany, Japan, the United Kingdom, and the United States support the view that exchange rate movements can be explained by the efficient or rational adjustment of foreign exchange markets to economic fundamentals. In the long run, the exchange rate is determined consistent with a monetary approach to exchange rates, while cyclical factors have an impact on short-run exchange rate dynamics. Estimated equations outperform random walk models of exchange rates.